Media Voices and Power: A decolonial analysis of black voices in the post-apartheid South African media landscape using City Press newspaper as an analytical focus - Mgibisa, Mbuyisi (University of the Witwatersrand, Johannesburg, 2023)
This study conducts a decolonial analysis of black voices in the post-apartheid South African media landscape using City Press newspaper as an analytical focus. For the purposes of this study, I have analysed four case studies linked to the mediation and meditation of black voices in the media and public sphere. First, this study explores the subjection of black voices inside the newsroom using the black-oriented newspaper, City Press, as an example. It assesses the structure of whiteness in that newspaper and interrogate whether it provided its black journalists with a room to write from the standpoint of “black perspective”. The second theme is an exploration and personal account of my lived experience in the typical South African neoliberal newsroom and an attempt to bring theory in order to figure out my lived experience. Third, this thesis focuses on forms of gendered and racialised forms of subjection posed by the silencing of voices of black women journalists in the South African mainstream media, including social media. And the fourth theme looks at the importance and significance of voice or speech in doing politics in the post-apartheid South Africa and interrogates how the Economic Freedom Fighters’ (EFF) has deployed its “radical black voice” through the concept of Black rage. The study utilises decolonial theory and Steve Biko’s Black Consciousness philosophy as a lens as it seeks to investigate how essentialised, racialised, politicised, gendered and lived are black voices in post 1994 South Africa media landscape and public sphere. This study, then, involves the critical analysis of four themes, all of which are integrally related. The main argument advanced in this thesis is that black voices continue to be subjected through the concept and function of coloniality. For this reason, the study not only historizes black voices as producers, users and custodians of knowledge but also situates their lived experiences. This study finds that even in the face of debilitating coloniality in our everyday lives, black voices persist through those politicised, gendered, racialised and lived negative forms of invisibility and marginalisation and think and speak from the perspective of blackness. Therefore, this thesis posits that black voices are a communicative plane on which blackness performs and articulate itself, for itself. Moreover, this study is a form of epistemic protest against systematic and systemic silencing of black voices and an attempt to counter efforts of rendering black people, in particular black women, speechless. The transdisciplinary methodological approach deployed here is, first and foremost, embedded in the theoretical framework and various methods and concepts will be operationalised to bring to light the complex and complicated nature of how black voices are mediated in the post-apartheid South African media landscape and public sphere. The interview method, which comprises a reflective commentary, and autoethnography are important components of this study. Additionally, the empirical findings through interview material, newspaper articles and tweeter feeds have been examined through discourse analysis and through the prism of the conceptual analytical tools deployed here.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the degree of Doctor of Philosophy in the field of Media Studies, in the School of Literature, Language and Media, in 2023.
Keywords: Black voices; South African media; City Press; Coloniality; Decolonial theory; Black Consciousness philosophy; UCTD; SDG-10: Reduced inequalities